(untitled) (Revista de Artes Marciales Asiáticas, 2026)
This paper aims to describe, contextualize and critically analyze the historical origin and background, circumstances, structure and logic that underpin Kodokan judo’s gokyo-no-waza and classification of throws outside of the gokyo. To do so, we have applied historical methods and source criticism allowing us to uncover hitherto unknown facts and to offer a critical analysis of the gokyo’s foundations and previously published hypotheses. With kata prior to the creation of the gokyo being the only crutch that Kano’s assistants could lean on when having to teach the Kodokan’s exponentially growing number of judo students, there was a dire need for a didactically organized teaching plan of technical progression. It is to that end that in 1895 some of Kano’s most senior students and himself came up with the gokyo-no-waza or “techniques of the five teachings” as their standard syllabus of throwing techniques. Today referred to as the kyu gokyo-no-waza, this first syllabus consisted of 42 techniques. In response to the evolution of judo, a revised syllabus, the shin gokyo-no-waza consisting of 40 techniques was launched in 1920 based on the input of six of Kano’s leading students. The techniques within the gokyo are organized foremost with attention to being easy for breakfalling. Between 1982 and 2017, the Kodokan expanded their syllabus to 68 throws by creating two categories of techniques outside of the gokyo, i.e. the habukareta-waza and the shinmeisho-no-waza. In this paper we propose to add a new category of 25 historically documented judo throws, which we have named the jidai-okure-no-waza [obsolete techniques] hence bringing the total recognized judo throws to 93.